Uji efektivitas ekstrak kunyit (Curcuma longa) terhadap daya hambat pertumbuhan bakteri Streptococcus mutans - I Nyoman Candra Kumara; I Gusti Agung Sri Pradnyani; I Gusti Ayu Fienna Novianthi Sidiarta (DiscoverSys Inc., 2019)
Background: Dental caries is a multifactorial disease characterized by dental tissue damage caused by the production of bacterial acids. The bacteria play the most role in the occurrence of caries is Streptococcus mutans. Turmeric extract (Curcuma longa) has been studied can inhibit bacterial growth because it contains essential oils and curcumin. The purpose of this study was to determine the inhibitory power of turmeric extract 5%, 10%, 20%, and 40% on the growth of Streptococcus mutans bacteria.Methods: Studies with true experimental design using a post test only control group design have been carried out on Streptococcus mutans bacteria. Turmeric extract was made by maceration method into 96% ethanol so that the required concentration was obtained (5%, 10%, 20%, dan 40%). The inhibition testing is done by the disk-diffusion method. Data were analyzed using the Kruskal-Wallis test on SPSS version 20 due to the data were not normally distributed.Results: The results showed that phytochemical assessment of turmeric extract showed positive results on phenol, essential oil, saponins, tannins, and flavonoids. The average value of the inhibitory zone diameter of Streptococcus mutans bacteria formed in turmeric extract concentrations of 5%, 10%, 20%, and 40% is 0 mm where there are significant differences compared to positive controls (P < 0.05)Conclusion: Various doses of turmeric extract couldnâ€™t inhibit the growth of Streptococcus mutans bacteriaÂ